Advances in conceptual modeling ER 2012 Workshops CMS, ECDM-NoCoDA, MODIC, MORE-BI, RIGIM, SeCoGIS, WISM, Florence, Italy, October 15-18, 2012, proceedings - International Conference on Conceptual Modeling (Information systems and applications, incl. Internet/Web, and HCI, 2012)
This book constitutes the refereed proceedings of workshops, held at the 31st International Conference on Conceptual Modeling, ER 2012, in Florence, Italy in October 2012. The 32 revised  papers presented together with 6 demonstrations were carefully reviewed and selected from 84 submissions. The papers are organized in sections on the workshops CMS 2012, EDCM-NoCoDa, MODIC, MORE-BI, RIGIM, SeCoGIS and WISM. The workshops cover different conceptual modeling topics, from requirements, goal and service modeling, to evolution and change management, to non-conventional data access, and they span a wide range of domains including Web information systems, geographical information systems, business intelligence, data-intensive computing. CMS 2012-Third International Workshop on Conceptual Modelling of Services -- Preface to CMS 2012 -- Session I: Ontologies and web applications -- A rule based approach for mapping sensor data to ontological models in AAL environments -- Session II: services and cloud computing -- Parameters for service level agreements Generation in cloud computing: a client-centric vision -- Resource, process, and use-views on service modeling -- A client-centric ASM-based approach to identity management in cloud computing -- ECDM-NoCoDa 201-first international workshop on evolution and change in data management and on non conventional data access -- Preface to ECDM-NoCoDA 2012 -- Session I: evolution and change in data management -- The telic/atelic distinction in temporal Databases (Keynote Paper) -- Static analysis of XML document adaptations -- Supporting database Provenance under schema evolution -- Session II: non conventional data access -- An in-browser microblog ranking engine -- Contextual recommendations for groups -- MoDIC 2012-first International Workshop on Modeling for Data-Intensive Computing -- Preface to MoDIC 2012 -- Session I: big data: general issues and modeling approaches -- A scientific hypothesis conceptual model -- An integrated multidimensional modeling approach to access big data in business intelligence platforms -- Session II: ontologies and conceptual models -- A comprehensive model for provenance (invited paper) -- Towards discovering ontological models from big RDF data -- Towards salable information modeling of requirements architectures -- MORE-BI 2012-Second International Workshop on Modeling and Reasoning for Business Intelligence -- Preface to MORE-BI 2012 -- OLAP-like analysis of time point-based sequential data -- Multi-dimensional navigation modeling using BI analysis graphs -- Ontology alignment for semantic data integration through foundational ontologies -- RIGiM 2012 − Fourth International Workshop on Requirements, Intentions and Goals in Conceptual Modeling -- Preface to RIGiM 2012 -- Where did the requirements come from? A retrospective case study -- Requirements, intentions, goals and applicable norms -- Towards advanced goal model analysis with jUCMNav -- SeCoGIS 2012-Sixth International Workshop on Semantic and Conceptual Issues in GIS -- Preface to SeCoGIS 2012 -- Session I: new frontiers of spatio-temporal -- Dimensions -- Key ingredients for your next semantics elevator talk (keynote paper) -- Towards a spatio-temporal form of entropy -- Session II: semantic issues -- The similarity jury: combining expert judgements on geographic concepts -- Enriching SQWRL queries in support of geospatial data retrieval from multiple and complementary sources -- From polygons and timestamps to dynamic geographic features: grounding a spatio-temporal geo-ontology -- Claudio E.C. Campelo, Brandon Bennett, and Vania Dimitrova -- Session III: conceptual issues. User view of spatial networks in spatial database systems -- A collaborative user-centered approach to fine-tune geospatial database design -- Using the DBV model to maintain versions of multi-scale geospatial data -- Session IV: spatio-temporal issues -- Multi-scale windowing over trajectory streams -- A geographic standards based metamodel to formalize spatio-temporal knowledge in remote sensing applications -- A fuzzy spatio-temporal-based approach for activity recognition -- WISM 2012-Ninth International Workshop on Web -- Information systems modeling preface to WISM 2012 -- Session I: web information systems development and analysis models -- Lightweight semantics over web information systems content employing knowledge tags (keynote paper) Investigating the relation between Users’ cognitive Style and web navigation behavior with K-means clustering -- Session II: web technologies and applications -- Web navigation via semantic annotations -- Using the web to monitor a customized unified financial portfolio -- Financial events recognition in web news for algorithmic trading -- ER 2012-demonstrations -- Alf-verifier: an eclipse plugin for verifying Alf/UML executable models -- A web-based filtering engine for understanding event specifications in large conceptual schemas -- An eclipse plugin for improving the quality of UML conceptual schemas -- Requirement-driven creation and deployment of multidimensional and ETL designs -- STS-tool: using commitments to specify socio-technical security requirements -- CAWE DW documenter: a model-driven tool for customizable ETL documentation generation.